ADHD – diagnosis and teacher's role (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder appeared in the medical literature in the mid-19th century and underwent numerous nomenclature changes until the current official term, through the DSM-V. Being a neurobiological disorder of genetic causes, the disorder has three main symptoms which are: hyperactivity, inattention and impulsivity and its conceptualization relates to psychiatry, psychology and education, as school is the first place where symptoms are evident and can be better observed. The specifics of diagnosis and diagnostic evaluation make the teacher play a fundamental role in the process, being responsible for the notes and observations about the symptoms presented. The present study aims to describe the role of the teacher in the diagnosis of ADHD. To this end, qualitative research was used as a methodology, in relation to the objectives, exploratory and descriptive, and with regard to research procedures, the study was characterized as bibliographic. The research was carried out in a virtual environment, in reliable databases such as Scielo, with scientific articles, books in PDF format, publications and conference proceedings, with the descriptors ADHD, diagnosis, professor. After the search and analysis, the results and discussion are divided into three topics, namely: The disorder, the specifics in the diagnosis and the role of the teacher in the diagnosis of ADHD. The author's conclusions and impressions comprise the final considerations.